2019
DOI: 10.1017/jfm.2019.567
|View full text |Cite
|
Sign up to set email alerts
|

Common features between the Newtonian laminar–turbulent transition and the viscoelastic drag-reducing turbulence

Abstract: The transition from laminar to turbulent flows has challenged the scientific community since the seminal work of Reynolds (Phil. Trans. R. Soc. Lond. A, vol. 174, 1883, pp. 935–982). Recently, experimental and numerical investigations on this matter have demonstrated that the spatio-temporal dynamics that are associated with transitional flows belong to the directed percolation class. In the present work, we explore the analysis of laminar–turbulent transition from the perspective of the recent theoretical dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
(152 reference statements)
2
23
0
Order By: Relevance
“…Velocity gradient is again decreased and the hibernating turbulence state rediscovered. This state is synonymous with reduced viscous stresses thereby increasing the potential for increased perturbation . The similarity between Newtonian laminar‐turbulent transitional flows and drag‐reduced turbulent flows led to the conjecture that viscous effects (Lumley's theory) was more pronounced than elastic effects in the complex mechanism of DR. Other numerical studies have highlighted the important role of polymer elasticity and a description of elastic‐inertia turbulence .…”
Section: Piv Investigations Of Drag‐reducing Flowsmentioning
confidence: 99%
See 4 more Smart Citations
“…Velocity gradient is again decreased and the hibernating turbulence state rediscovered. This state is synonymous with reduced viscous stresses thereby increasing the potential for increased perturbation . The similarity between Newtonian laminar‐turbulent transitional flows and drag‐reduced turbulent flows led to the conjecture that viscous effects (Lumley's theory) was more pronounced than elastic effects in the complex mechanism of DR. Other numerical studies have highlighted the important role of polymer elasticity and a description of elastic‐inertia turbulence .…”
Section: Piv Investigations Of Drag‐reducing Flowsmentioning
confidence: 99%
“…The recent shift from the traditional view off transition as merely a change from linear to nonlinear dynamics has been shown (by numerical simulation) to extend to viscoelastic drag‐reducing flows. Numerical simulation studies, such as that of have demonstrated interesting similarities between Newtonian laminar‐turbulent transitional flow and drag‐reduced viscoelastic flows, however, there are gaps that can be filled by both numerical simulation and experimental studies (such as PIV technique). These include: Dimensionless parametrization of the common characteristics of these two types of flow. Comparison between both types of flow at similar wall friction (DR). Connection between hibernating turbulence state and high‐DR as well as the active turbulence state and low‐DR. Comparison of the low‐DR and high‐DR limits of both flows.…”
Section: Research Gapsmentioning
confidence: 99%
See 3 more Smart Citations